AKIBAT HUKUM DELISTING TERHADAP PERSEROAN TERBUKA - Wahyuni, Rani Eka (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
The capital market is one of the alternative sources of funding for both the government and the private sector, so to develop a country's national economy, financing is needed from both the government and the community. In recent years, Indonesia has experienced a significant increase in the number of retail investors in the capital market. In 2020, the number of capital market investors in Indonesia surged by more than 56%, reaching over 3.87 million investors. This growth has been driven by increased accessibility to technology and online trading platforms, which have made it easier for the public to invest. Meanwhile, initial public offerings (IPOs) from companies such as PT Bukalapak and PT GoTo have also had a major impact on increasing market liquidity, although some IPOs have faced challenges related to stock valuations. The issue raised in this research concerns the delisting of publicly listed companies, which has significant implications for investors, particularly in relation to legal protection and the return on investment during forced delisting. Delisting can lead to the loss of stock liquidity and losses for investors who can no longer trade their shares on the regular market. This study aims to examine the legal basis for delisting publicly listed companies and legal protection for investors, as well as to explore dispute resolution efforts that can be undertaken by investors harmed by delisting, using a normative juridical approach. Data collection is conducted through literature studies with primary, secondary, and non-legal sources. This study finds that delisting can have adverse effects on investors, as delisted stocks can no longer be traded normally, leading to the potential for significant losses. However, legal protection for investors in such cases is provided through mechanisms such as the negotiation market and share buybacks by delisted companies, as regulated by the Financial Services Authority. Keywords: Public Company, Go Public, Delisting